Songlines - Sotiris Kampanelis; Aldo Elizalde; Yannis M. Ioannides (Queen's University Centre for Economic History (QUCEH), 2023)
This paper examines the long-term economic impacts of the adoption of local knowledge during European colonisation. We use the case of Australia, where Aboriginal knowledge of the landscape was integral to colonial exploration and settlement. To quantify the effects of this knowledge, we construct a newly digitised and georeferenced dataset of trade routes created by Aboriginal people based on oral traditions, known as Songlines. Our results indicate that Aboriginal trade routes are strongly associated with current economic activity as measured by nighttime satellite imagery. We attribute this association to path dependence and agglomeration effects that emanate from the transport infrastructure built by Europeans roughly along these routes, which have agglomerated economic activity. Finally, by exploiting exogenous variation in optimal travel routes, we provide evidence that our results are not entirely determined by the inherent characteristics of Australian topography, but rather by Aboriginal knowledge.
Keywords: N77; O10; R12; Z10; Z13; 330; Aboriginal trade routes; Songlines; colonialism; agglomeration; Australia